Abdurrahman An-Nashir's Role in Advancing Development and The Splendor of Islamic Architecture in Andalusia - Nurul Ainiy (JUSPI (Jurnal Sejarah Peradaban Islam), 2022)
Andalusia is one of the most magnificent centers of Islamic civilization. Its beauty is said to be able to match the beauty of Baghdad and Constantinople. This makes Andalusia as one of the centers of world civilization. Physical and architectural development in Andalusia advanced and developed during the leadership of Abdurrahman An-Nashir (912-961M). This is because apart from being proficient in politics, Abdurrahman III is also known to be proficient in the field of development planning. This study aims to explore further the role of Abdurrahman An-Nashir in advancing architecture in Andalusia, as well as the impact of these advances in various fields. Some of An-Nashir's efforts in advancing Andalusian architecture were urban planning, building mosques, building palaces, and establishing universities and libraries. This policy has positive impacts in various fields, including advancing the education sector, improving the economy, maintaining government stability, and contributing to the legacy of civilization.